Employment polarization and the role of the apprenticeship system - Michelle Rendall; Franziska J. Weiss (University of Zurich, Department of Economics, 2014)
This paper studies the effects of the apprenticeship system on innovation and labor market polarization. A stylized model with two key features is developed: (1) apprentices are more productive due to industry-specific training, but (2) from the firm's perspective, when training apprentices, technological innovation is costly since training becomes obsolete. Thus, apprentices correlate with slower adoption of skillreplacing technologies, but also less employment polarization. We test this hypothesis on German regions given local variation in apprenticeship systems until 1976. The results shows no employment polarization related to apprentices, but similar displacement of non-apprentices as in the US.
Keywords: E24; I24; J24; J62; O33; 330; Apprentices; educational system; employment polarization; technology adoption